Economic Models of the Labor Market and Pension Accounting: An Exploratory Analysis. - Pesando, James E.; Clarke, Carol K. (The Accounting Review, 1983)
ABSTRACT: This paper argues that the analysis of the tradeoff between current wages and pension benefits offers key insights into the problem of pension accounting. The paper examines this tradeoff under two "polar" models of the labor market, a spot model and a lifetime contract model. Using the matching principle, the paper then examines–for each model–three important issues in pension accounting. They are: (1) the use of accrued versus projected benefit valuation methods; (2) the distinction between vested and non-vested pension benefits; and (3) the treatment of pension liabilities created through retroactive plan amendments. The models differ in their implications for (1) and (2), Both models suggest that the extended amortization of liabilities created through retroactive plan amendments may be inappropriate.